Corrigendum: Warm-Up Stretching Exercises and Physical Performance of Youth Soccer Players (Frontiers in Physiology, 2023 14 1127669 10.3389/Fphys.2023.1127669) - Herrera-Valenzuela, T (Frontiers Media S.A., 2023)
In the published article, there was an error regarding the affiliation(s) for Jordan Hernandez-Martinez; Tiago Vera-Assaoka. As well as having affiliation 1 Universidad de Los Lagos, Osorno, Chile; 2 Department of Physical Activity Sciences, Universidad de Los Lagos, Osorno, Chile; they should also have “3 Programa de Investigación en Deporte, Sociedad y Buen Vivir, Universidad de Los Lagos, Osorno, Chile”. In addition, there was an error regarding the affiliation(s) for Bastian Carter-Thuillier. As well as having affiliation 5 Department of Education, Universidad de Los Lagos, Osorno, he should also have “3 Programa de Investigación en Deporte, Sociedad y Buen Vivir, Universidad de Los Lagos, Osorno, Chile; 6 Universidad Católica de Temuco, Temuco, Chile”. In the published article, an author name was incorrectly written as Bastian Carter-Trullier. The correct spelling is “Bastian Carter-Thuillier”. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated. Copyright © 2023 Hernandez Martinez, Ramirez-Campillo, Vera-Assaoka, Castillo Cerda, Carter-Thuillier, Herrera-Valenzuela, López-Fuenzalida, Nobari and Valdés-Badilla.